Disability and the Family in South Wales Coalfield Society, c.1920–1939. (2nd January 2017) - Curtis, Ben; Thompson, Steven
Abstract : This article utilises the south Wales coalfield in the interwar period as a case study to illustrate the applicability of two sociological theories – family systems theory and the social ecology of the family – to impairment in the past. It demonstrates that a theoretically-informed approach can help to situate impairment in its particular contexts, most especially the family and the community, and give a better sense of the lived experience of disability. It also demonstrates the complexity of the experience of disability as the family and economic circumstances of each impaired individual varied and led to different forms of care-giving or the utilisation of different sources of support. The article also sheds further light on the ubiquity of disability as many families included a number of individuals with different impairments and this too had consequences for experiences and coping strategies.